2010
DOI: 10.1186/1744-8069-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adeno-Associated Virus Mediated Gene Transfer to Sensory Neurons following Intrathecal Delivery by Direct Lumbar Puncture

Abstract: BackgroundNeuronal transduction by adeno-associated viral (AAV) vectors has been demonstrated in cortex, brainstem, cerebellum, and sensory ganglia. Intrathecal delivery of AAV serotypes that transduce neurons in dorsal root ganglia (DRG) and spinal cord offers substantial opportunities to 1) further study mechanisms underlying chronic pain, and 2) develop novel gene-based therapies for the treatment and management of chronic pain using a non-invasive delivery route with established safety margins. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 37 publications
7
107
3
Order By: Relevance
“…Although gene expression was found in the sciatic nerve after AAV vector delivery into the DRG, this was mainly in axons and DRG, and not in Schwann cells as in our study (23). Cell specificity is crucial for exogenous expression of neuropathy-associated genes such as Cx32, given that inherited demyelinating neuropathies result mostly from cell-autonomous loss of function in Schwann cells (35,36).…”
Section: Discussionmentioning
confidence: 75%
“…Although gene expression was found in the sciatic nerve after AAV vector delivery into the DRG, this was mainly in axons and DRG, and not in Schwann cells as in our study (23). Cell specificity is crucial for exogenous expression of neuropathy-associated genes such as Cx32, given that inherited demyelinating neuropathies result mostly from cell-autonomous loss of function in Schwann cells (35,36).…”
Section: Discussionmentioning
confidence: 75%
“…1I ). It has been reported that drugs can be predominantly delivered into DRG neurons by direct lumbar puncture (Vulchanova et al, 2010;Duan et al, 2012). LP injection of SD-208 (5 g/20 l) had no effect on PWL in naive rats (Fig.…”
Section: Tgf-␤1 and Tgf␤rs Are Involved In Bone Cancer Painmentioning
confidence: 99%
“…Here the potential role of the pia mater in establishing such a barrier to particulates and larger molecules in the CSF has been noted in humans and dogs [438][439][440]. Techniques to increasethat movement have been proposed,including the use of hypertonic solutions [441].…”
Section: Gene-based Approachesmentioning
confidence: 99%